The efficacy of the method for producing micro-preparations from Ctenocephalides felis fleas, which parasitize on cats - Melnychuk, V.; Havryk, B. (Scientific Progress & Innovations, 2025)
Fleas of the genus Ctenocephalides attack mammals such as carnivores, lagomorphs, marsupials, primates, rodents, and ungulates. Among arthropods, the fleas of Ctenocephalides felis species are the most important ectoparasites of cats worldwide, which negatively affect the animal’s body and are carriers of dangerous diseases. The parasites cause allergic dermatitis, anemia, especially in young animals. Therefore, timely detection and identification of ctenocephalidosis pathogens is relevant, the effectiveness of which depend on the high-quality production of preparations of micro-preparations from parasitic insects. The aim of the work was to improve and test the method for making micro-preparations from C. felis fleas, which parasitize on cats. The study was conducted in the conditions “Yashma” private veterinary clinic (the city of Kremenchuk) and the laboratory of the Department of Parasitology and Veterinary and Sanitary Expert Examination of Poltava State Agrarian University (the city of Poltava). The proposed method is related to veterinary medicine, namely veterinary parasitology, and can be used for making anatomical and morphological preparations from C. felis fleas with the aim of studying their morphological and metric features in the structure. It was found that the use of the proposed method for making total micro-preparations from fleas turned out to be more effective concerning the general assessment of the intensity of coloring of the fleas’ body morphological structures (by 72.51 %, P<0.001) and the time required to make one micro-preparation (by 80.39 %, P<0.001) compared to similar indicators in the method of preparing pathogens of Mallophaga order in toto. The use of the proposed method allowed to obtain good, uniform coloring of all the fleas’ antennal segments, as evidenced by the obtained high average score (4.91). At the same time, the use of the method of preparing the pathogens of Mallophaga order in toto led to oversaturation of the above-mentioned morphological structures with dye, as indicated by the obtained low score (1.35). The obtained results allow us to recommend the proposed method of producing micro-preparations from Ctenocephalides felis fleas to increase the efficacy of microscopic studies for feline ctenocephalidosis.